2001
DOI: 10.1046/j.1365-2516.2001.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraleucocyte platelet‐activating factor levels in desmopressin‐treated patients with haemophilia A and von Willebrand disease

Abstract: Despite the intensive clinical use of 1-deamino-8-D-arginine vasopressin (desmopressin; DDAVP) for 20 years, its mechanism of action is still not completely explained. It has been proposed that DDAVP stimulates release of a 'second messenger' which in turn stimulates release of von Willebrand factor (vWF) from endothelial cells. Platelet-activating factor (PAF) and interleukin (IL)-6 were individually proposed to be mediators for haemostatic action. The aim of this study was to investigate cellular-based PAF l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Blood monocytes possess V2 receptors and can bind DDAVP (Block et al , 1981), and Hashemi et al (1990, 1993) have shown that monocytes exposed to DDAVP release platelet‐aggregating factor (PAF) into culture supernatants, which in turn induces the release of VWF from endothelial cells. Consistent with these in vitro findings, increased levels of PAF have been found within leucocytes after administration of DDAVP to patients with haemophilia A or VWD (Kavakli et al , 2001). All these findings suggest that intercellular messengers, secreted by monocytes, may play a role in the haemostatic effect of DDAVP.…”
supporting
confidence: 74%
“…Blood monocytes possess V2 receptors and can bind DDAVP (Block et al , 1981), and Hashemi et al (1990, 1993) have shown that monocytes exposed to DDAVP release platelet‐aggregating factor (PAF) into culture supernatants, which in turn induces the release of VWF from endothelial cells. Consistent with these in vitro findings, increased levels of PAF have been found within leucocytes after administration of DDAVP to patients with haemophilia A or VWD (Kavakli et al , 2001). All these findings suggest that intercellular messengers, secreted by monocytes, may play a role in the haemostatic effect of DDAVP.…”
supporting
confidence: 74%
“…Mannucci in 1997 reported that a FVIII:C level of ‡0.30 U mL )1 is sufficient to treat minor bleeds or to prevent bleeding in minor surgery [17]. Others have suggested that to be labelled as responders to DDAVP, patients need to attain a FVIII:C level of at least 0.50 U mL )1 [18,19]. In this study, we defined responders to DDAVP as those patients achieving a FVIII:C level of ‡0.30 U mL )1 one-hour post DDAVP infusion.…”
Section: Definition Of Ddavp Responsementioning
confidence: 99%
“…It was also suggested that some are derived from WBC, such as platelet-activating factor (PAF), interleukin (IL)-6, or P-selectin (Hashemi et al 1993, Mannucci 1997. In particular, PAF is a potent activator of both WBC and PLT (Kavakli et al 2001), and P-selectin plays an important part in the "rolling" of polymorphonuclear leucocytes (PMN), as demonstrated in the mesenteric venules of rats (Kanwar et al 1995).…”
Section: Discussionmentioning
confidence: 99%